2016
DOI: 10.1089/end.2015.0673
|View full text |Cite
|
Sign up to set email alerts
|

Post-Chemotherapy Robotic Retroperitoneal Lymph Node Dissection: Institutional Experience

Abstract: Robotic PC-retroperitoneal lymph node dissection (RPLND) is technically feasible and with acceptable morbidity. It is associated with low blood loss and short hospital stay. More research is needed to assess the long-term outcome and to compare standard open RPLND.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 22 publications
0
33
0
Order By: Relevance
“…There are only a few studies, which reported experience of RA-RPLND for postchemotherapy residual mass. [ 7 16 17 18 ] Although these are retrospective studies and had small number of patients, they reported acceptable surgical and oncologic outcome. Our study of 13 patients is the largest one to best of our knowledge with retrospective and prospective follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…There are only a few studies, which reported experience of RA-RPLND for postchemotherapy residual mass. [ 7 16 17 18 ] Although these are retrospective studies and had small number of patients, they reported acceptable surgical and oncologic outcome. Our study of 13 patients is the largest one to best of our knowledge with retrospective and prospective follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the favorable outcomes of L-RPLND in the postchemotherapy setting [ 42 ], the natural evolution of the R-RPLND has included attempts by experienced robotic surgeons to perform postchemotherapy R-RPLND (PC-RPLND) in selected patients. To date, only two smaller series have demonstrated early feasibility [ 12 , 32 ]. The Mayo Clinic R-RPLND experience included nine patients who were postchemotherapy.…”
Section: Postchemotherapy Rplndmentioning
confidence: 99%
“…The advantages of R-RPLND over L-RPLND were similar to other urologic operations that transitioned to a robotic approach: a reduced learning curve, three-dimensional visualization, and greater instrument dexterity from the wristed instruments. Boosted by early results demonstrating equivalence in oncologic and safety measures compared to open and laparoscopic approaches, the R-RPLND has become an excellent option for the treatment of CS I and CS II nonseminomatous GST (NSGCT) and is emerging as a feasible approach for postchemotherapy RPLND [ 12 ]. In this article, we will review the technique and early outcomes of R-RPLND as compared to both O-RPLND and L-RPLND for the management of primary low-stage nonseminomatous and postchemotherapy GCT.…”
Section: Introductionmentioning
confidence: 99%
“…Most of these cases were related to primary RPLND, whereas other investigations were related to salvage RPLND for residual tumor following chemotherapy [12,13,14]. Different patient positions and port configurations have been described, with different indications, advantages and disadvantages.…”
Section: Introductionmentioning
confidence: 99%